Towards a Transcendental Critique of Feeling (A Response to Grenberg) - Frierson, Patrick (Con-Textos Kantianos. International Journal of Philosophy, 2016)
This paper focuses on responding to Jeanine Grenberg’s claim that my discussion of Kant’s feeling of respect leaves no meaningful room for investigating feeling first-personally. I first make clear that I do think that feelings can be investigated first-personally, both in that they can be prospective reasons for action and in that – at least in Kant’s Critique of the Power of Judgment – there are feelings that we should have (for aesthetic reasons). I then show that at the time of writing the “Incentives” chapter of the second Critique, Kant had not yet determined an a priori basis for aesthetic (or affective) normativity. On this basis, I argue that the “Incentives” chapter provides a sort of consolation prize for not (yet) having an transcendental account of feeling. In that sense, it’s a properly transcendental analysis of feeling in which Kant examines feeling from within and a priori to show that there are good (moral) reasons to have certain feelings. I end by acknowledging the extent to which, on this reading, I agree with Grenberg that Kant is doing a transcendentally significant form of phenomenology here, while I also highlight some remaining areas of disagreement.
Keywords: Kant; Phenomenology; Moral Feeling; Empirical Psychology